PENGARUH VIDEO EDUKATIF “AKU SIAP, AKU SELAMAT” TERHADAP PENINGKATAN PEMAHAMAN MITIGASI BENCANA BAGI SISWA TUNAGRAHITA DI SLB - Yuniar, Nisa; Idhartono, Amelia Rizky; Jauhari, Muhammad Nurrohman (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This research is motivated by the low understanding of students with intellectual disabilities at Batu State Special Needs School regarding the risks and mitigation of natural disasters, even though they are located in a geographical area prone to flash floods. This lack of knowledge creates a serious safety threat due to unpreparedness for emergency situations. The focus of this study is to evaluate the effect of the educational video entitled "I'm Ready, I'm Safe" on improving students' disaster mitigation literacy. The study applied a quantitative method with a one-group pretest-posttest pre-experimental design. The research steps included administering an initial test (pretest), providing treatment through showing the educational video six times, and a final test (posttest). Data were analyzed using a statistical sign test. The results showed a significant increase in students' understanding, where the average pretest score of 12.5 increased drastically to 92.5 in the posttest. The statistical analysis produced a calculated Z value of 2, which exceeds the critical Z table value of 1.96 at a 5% significance level. The main conclusion is that the educational video "I'm Ready, I'm Safe" has a significant effect on improving students' understanding of disaster mitigation. This media has proven to be effective as a concrete and representative learning tool in helping students with intellectual disabilities understand safety procedures through attractive, easy-to-understand visualizations to strengthen their preparedness at school in a real and appropriate manner for the safety of students in the future.